Enhancing resilience in the Horn of Africa: An exploration into alternative investment options - Headey, Derek D.; Taffesse, Alemayehu Seyoum; You, Liangzhi (International Food Policy Research Institute, 2012)
The most recent (2010–2011) drought in the arid and semiarid lowlands (ASAL) of the Horn of Africa has rendered over 13 million people in need of food, and caused a devastating famine in southern Somalia. The drought has also raised concerns that pastoralist livelihoods in this region are no longer viable or sustainable, thereby justifying strategies that aim to sedentarize and diversify these livelihoods. Countering this view are advocates of wholesale protection of pastoralist livelihoods. Yet despite these very contrasting views on economic development in the region, very little research directly addresses this big picture question of where public resources should be invested. In this paper we argue that both economic theory and the existing evidence base warrant a more balanced development strategy involving movement out of pastoralism (intersectoral transformation), modernization of pastoralism (intrasectoral transformation), and cross-cutting transformations of the demographic, social, and political structure of ASAL populations. We then explore the empirical basis for balancing investments across these kinds of transformations. While the available evidence base is weak in some respects, we find that most nonpastoralist livelihoods in ASAL yield lower incomes than pastoralism, with the exception of urban livelihoods and irrigated farming. However, both irrigation and urban migration have a limited capacity to absorb growing populations. Additional irrigation investments in pastoralist regions, for example, appear to be capable of profitably absorbing only about three percent of the estimated pastoralist population in 2020. Migration is more promising, but only provided that it comes on the back of much larger investments in education and meaningful urban job opportunities.